Supratip-Plasty: A Completely Cartilaginous Tip Complex to Maintain Nasal Tip Width. (January 2014) - Gruber, Ronald P.; Kwon, Edwin; Berger, Aaron; Belek, Kyle A.
Background: Following primary rhinoplasty, the nasal tip may become wider on front view, possibly due to splaying of the lateral crura. Objectives: The authors describe a technique, the "supratip-plasty, " to create an all-cartilaginous supratip that resists splaying and postoperative broadening of the nasal tip complex. Methods: Thirteen consecutive primary rhinoplasty patients (10 women; 3 men) with broad nasal tips received a supratip-plasty (which preserved the cephalic part of the lateral crus, reducing it in size and securing it to the dorsal septum, resulting in a completely cartilaginous tip framework) and were followed for 11 to 17 months. Since the frontal tip width (TW) is relative to the frontal nasal base width (NBW), the TW/NBW ratio was contrasted to that of 19 unoperated aesthetically pleasing nasal tips. Results: Of the 13 cases, all but 1 were considered to have a good result. The preoperative mean TW/NBW ratio was 0.68. The postoperative mean was 0.53, compared with 0.48 in the unoperated aesthetic tip group. No tip revisions were necessary; however, 2 patients did require revisionary surgery for nontip problems. Conclusions: Preserving a cephalic island of lateral crus, trimming it to fit the new supratip contour following suture tip-plasty, and securing it to the septum provides a completely cartilaginous nasal tip framework that tends not to widen postoperatively. Level of Evidence: 4